Factors Surrounding the Healthcare Transition From Pediatric to Adult Care in 5p- Syndrome: A Survey Among Healthcare Professionals - Ishizaki, Yuko; Matsuo, Mari; Saito, Kayoko; Fujihira, Yoko (Frontiers in Pediatrics, 2022)
Background The 5p- syndrome is associated with intellectual disturbance and physical complications from infancy, and patients continue treatment into adulthood. This study aimed to clarify the factors that facilitate and prevent healthcare transition from pediatric to adult care by conducting a questionnaire survey among medical professionals. Subjects The survey included 81 medical professionals nominated by an association of families of 5p- patients in Japan. The questions involved medical care for 5p- syndrome in adulthood, experience of transition, and factors facilitating a patient’s transition. Responses were obtained from 32 participants, with 27 answers eligible for analysis. Results The questionnaire items involved physical symptoms and concerns regarding support and welfare prompting consult. The most common physical symptom was constipation. Regarding support and welfare, all participants had an experience of receiving consultation about care for the siblings of patients. Three (11.1%) participants had an experience of transition. Regarding the transition of patients with rare diseases or intellectual disturbance, only four (14.8%) believed that progress was being made in the transition. Discussion Only 11% of the respondents experienced the transition of patients with 5p- syndrome. Because it is difficult for highly specialized adult care providers to deal with multidisciplinary complications of 5p- syndrome and information on prognosis and natural history is not known, it is presumed that the transition of 5p- syndrome did not progress. Factors to improve the transition of patients with 5p- syndrome and are likely to be effective for the transition of patients with other rare diseases or intellectual disabilities.